2007
DOI: 10.1073/pnas.0609028104
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous IL-12 triggers an antiangiogenic program in melanoma cells

Abstract: The IL12RB2 gene acts as a tumor suppressor in human B cell malignancies. Indeed, Il12rb2 knockout (KO) mice develop spontaneously B cell tumors, but also lung epithelial tumors. This latter phenotype may be related to (i) impairment of host IL-12-mediated immunosurveillance and/or (ii) IL-12 inability to inhibit directly the growth of IL-12 unresponsive malignant cells. To address this issue, we transplanted IL-12R ؉ B16 melanoma cells into syngeneic Il12rb2 KO mice with the following rationale: (i) these mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 47 publications
3
68
0
Order By: Relevance
“…However recent data may allow reconsidering this cytokine as a therapeutic tool in selected tumor subsets. Actually it has been reported that the in vivo tumor response to IL-12 is influenced by the molecular features of its receptor [63] and that IL-12 could be a candidate for tumor shrinkage observed during the treatment of early-stage non-small cell lung cancer with tyrosine kinase inhibitors (vandetanib, pazopanib) targeting angiogenic receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…However recent data may allow reconsidering this cytokine as a therapeutic tool in selected tumor subsets. Actually it has been reported that the in vivo tumor response to IL-12 is influenced by the molecular features of its receptor [63] and that IL-12 could be a candidate for tumor shrinkage observed during the treatment of early-stage non-small cell lung cancer with tyrosine kinase inhibitors (vandetanib, pazopanib) targeting angiogenic receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…8 A BECN1 shRNA plasmid (SA Biosciences, KH05670N) and MTOR shRNA plasmid (Addgene, 1855) have been reported previously. 36,37 Briefly, transfection of a GFP-LC3 or BECN1 shRNA or negative control shRNA into SH-SY5Y cells was performed by using Lipofectamine 2000 (Invitrogen, 11668-019) according to the manufacturer's protocol. Forty-eight h after the transfection, the cells were subjected to immunofluorescent or immunoblotting analysis.…”
Section: Methodsmentioning
confidence: 99%
“…M.P. Colombo (Istituto Nazionale Tumori, Milano) and Guido Kroemer (INSERM, Paris, France), respectively, and extensively tested in the authors' laboratories (11,12). The N13 microglial cell was a kind gift of Dr. Paola Ricciardi-Castagnoli (Singapore Immunology Network, Singapore), and extensively tested in the authors' laboratory for cytokine and surface marker expression (13).…”
Section: Cell Culturesmentioning
confidence: 99%